2006
DOI: 10.1111/j.1444-2906.2006.01121.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of three GnRHs in the brain and pituitary of the wild Japanese flounder Paralichthys olivaceus

Abstract: Wild adult maturing and immature female Japanese flounder Paralichthys olivaceus were collected in June 2004 and January 2005, respectively, to clarify a possible role of gonadotropinreleasing hormones (GnRHs) in reproduction. Levels of salmon GnRH (sGnRH), chicken GnRH-II (cGnRH-II) and sea bream GnRH (sbGnRH) in the brain and pituitary were examined by time-resolved fluoroimmunoassay. Three forms of GnRHs were detected in the discrete brain at various levels. In the pituitary of both maturing and immature fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
1
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 32 publications
1
20
1
2
Order By: Relevance
“…Surprisingly no immunoreactive structures were found with anti sbGnRH serum although sbGnRH is thought to be the most important regulator of gonadal function (Lethimonier et al, 2004;Pham et al, 2006), and sbGnRH-producing cell bodies project their axons mainly to the pituitary gland (White et al, 1995;Gonzalez-Martinez et al, 2001).This negative result is of difficult interpretation despite the fact that different dilutions and incubation times were used in the experiments carried out here. The lack of anti sbGnRH immunostaining likely depends on technical reasons, including the non-specificity of the primary antibody used, as well as likely antigen damage during the fixation and paraffin wax embedding.…”
Section: Discussioncontrasting
confidence: 41%
See 2 more Smart Citations
“…Surprisingly no immunoreactive structures were found with anti sbGnRH serum although sbGnRH is thought to be the most important regulator of gonadal function (Lethimonier et al, 2004;Pham et al, 2006), and sbGnRH-producing cell bodies project their axons mainly to the pituitary gland (White et al, 1995;Gonzalez-Martinez et al, 2001).This negative result is of difficult interpretation despite the fact that different dilutions and incubation times were used in the experiments carried out here. The lack of anti sbGnRH immunostaining likely depends on technical reasons, including the non-specificity of the primary antibody used, as well as likely antigen damage during the fixation and paraffin wax embedding.…”
Section: Discussioncontrasting
confidence: 41%
“…In teleost fish, 8 GnRH variants have been identified, although two or three of the GnRH forms co-exist in the brain albeit distributed differently (Pham et al, 2006). Among the Pleuronectiforms and Perciformes, sea bream (sb)GnRH-producing cell bodies in the preoptic area project their axons mainly to the pituitary, whereas salmon sGnRHand chicken cGnRH-producing cells connect different areas of the brain through their axons, which, however, do not project to the pituitary (White et al, 1995;Gonzalez-Martínez et al, 2001;Amano et al, 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Into the GnRH1 line belong types such as mGnRH (Matsuo et al, 1971), seabream GnRH (Powell et al, 1994), catfish GnRH (Bogerd et al, 1992). They fulfil hypophysiotropic functions (Pham et al, 2006) and are found in the ventral telencephalon, the preooptic area, the basal hypothalamus and the pituitary gland (Dubois et al, 2002). Despite great effort, the occurrence of the GnRH1 line has not been detected in the cyprinids.…”
Section: Stimulation Factor Of Lh Secretion -Gnrhmentioning
confidence: 99%
“…Três principais isoformas do GnRH foram identificadas em pleuronectiformes: sGnRH (salmon GnRH), cGnRH-II (chicken GnRH-II) e sbGnRH (sea bream GnRH) (Amano et al, 2002;Pham et al, 2007), e a isoforma sbGnRH foi identificada como a provável responsável pela maturação gonadal (puberdade) nesses peixes (Amano et al, 2008). Além disso, a expressão desse gene parece não estar restrita ao sistema nervoso central dos peixes.…”
Section: Introductionunclassified